Patterns of Diseases among Children’s Pilgrims during Arba’een of Imam Hussein in Holy Kerbala City - Obaid, Khamees Bandar; Ajil, Zaid Waheed; Musihb, Zeki Sabah; Athbi, Hassan Abdullah; Al-Juboori, Ali Kareem Khudhair; Mahmood, Fatma Makee (International Journal of Psychosocial Rehabilitation, 2020)
Background: Arba’een is the biggest annual pilgrimage around the world, in which millions of Muslim’s pilgrims are gathering in kerbala city, at the Holly Shrine of Imam Hussain. During Arba’een of Imam Hussein there is a lot of children came to Karbala with their families. There are many pediatric diseases associated with travel or mass gathering, the risks that children face while travelling they are likely similar to their parents face. During the Arba’een of Imam Hussein there is no formal statistics or report about the common illness among children’s pilgrims in Karbala city. This study was focusing on the common diseases among children’s pilgrims attending to Holy Karbala at Arba’een of Imam Hussian. Objectives: The aims of the present study was to assess the common diseases among children’s pilgrim attending to Holy Kerbala during Arba’een of Imam Hussein, and to find out the relationships between socio- demographic variables such as child’s age, gender, and nationality with their diseases. Methodology: Quantitative cross-sectional study, conducted at three pediatric clinics from the period of 12th to 20th of Safar 1440 (22th-30th October 2018). A non-probability (convenience) sample consists of 350 children, ages 1-12 years came with their families to Holy Karbala city to participate in the Arba’een of Imam Hussein from Iraq and different countries were involved in this study. Results: The results of the present study indicate that the majority (77.1%), and (19.9%) of children pilgrims were from Iraq and Iran respectively, and more than one half (54.3%) of them have respiratory disorders. Recommendations: The researchers recommended the need for construct and apply a special instructional program for pilgrims about primary prevention of common diseases among children during Arba’een of Imam Hussian. Conclusion: Upper respiratory tract infection is the most common health problem among children pilgrims attending to Holy Kerbala in Arba’een of Imam Hussian.